Osteoblast and Osteoclast Activity Affect Bone Remodeling Upon Regulation by Mechanical Loading-Induced Leukemia Inhibitory Factor Expression in Osteocytes - Du, Jingke; Yang, Jiancheng; He, Zihao; Cui, Junqi; Yang, Yiqi; Xu, Mingming; Qu, Xinhua; Zhao, Ning; Yan, Mengning; Li, Hanjun; Yu, Zhifeng (Frontiers in Molecular Biosciences, 2020)
Purpose Bone remodeling is affected by mechanical stimulation. Osteocytes are the primary mechanical load-sensing cells in the bone, and can regulate osteoblast and osteoclast activity, thus playing a key role in bone remodeling. Further, bone mass during exercise is also regulated by Leukemia inhibitory factor (LIF). This study aimed to investigate the role of LIF in the mechanical response of the bone, in vivo and in vitro, and to elucidate the mechanism by which osteocytes secrete LIF to regulate osteoblasts and osteoclasts. Methods A tail-suspension (TS) mouse model was used in this study to mimic muscular disuse. ELISA and immunohistochemistry were performed to detect bone and serum LIF levels. Micro-computed tomography (CT) of the mouse femurs was performed to measure three-dimensional bone structure parameters. Fluid shear stress (FSS) and microgravity simulation experiments were performed to study mechanical stress-induced LIF secretion and its resultant effects. Bone marrow macrophages (BMMs) and bone mesenchymal stem cells (BMSCs) were cultured to induce in vitro osteoclastogenesis and osteogenesis, respectively. Results Micro-CT results showed that TS mice exhibited deteriorated bone microstructure and lower serum LIF expression. LIF secretion by osteocytes was promoted by FSS and was repressed in a microgravity environment. Further experiments showed that LIF could elevate the tartrate-resistant acid phosphatase activity in BMM-derived osteoclasts through the STAT3 signaling pathway. LIF also enhanced alkaline phosphatase staining and osteogenesis-related gene expression during the osteogenic differentiation of BMSCs. Conclusion Mechanical loading affected LIF expression levels in osteocytes, thereby altering the balance between osteoclastogenesis and osteogenesis.